Cocoa sector: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
ACP countries are world leaders in cocoa production, which is mainly concentrated in West and Central Africa. Increased price volatility, coupled with changing patterns in global demand and supply concerns, as well as the emergence of new non-ACP suppliers, constitute some of the main challenges that the cocoa sector in ACP countries has to address. This Executive Brief examines the main features of the 2012/2013 cocoa season, focusing on the main global trends and the implications for ACP producers. Special attention is also given to recent EU policy developments applying stricter food safety and sanitary and phytosanitary standards to imported cocoa beans, as well as the 2012/13 cocoa sector reforms in Côte d’Ivoire, which aimed at strengthening the functioning of the internal cocoa supply chain. Finally, the Brief highlights some opportunities for ACP cocoa market development in the near future, such as by meeting the growing demand in Asian countries (mainly China and India), the establishment of local value-adding processing facilities, and the possibility of receiving price premiums for single origin, organic and fair-trade certified cocoa.